Regulatory Aspects of Electronic Charting The Perspective of the United Kingdom Maritime and Coastguard Agency - Collins, Joe (The International Hydrographic Review, 2015)
The development of electronic charting systems is one of the most exciting applications of marine technology to have taken place since the widespread introduction of radar aboard merchant ships in the aftermath of World War II. Such systems bring a new dimension to bridge watchkeeping and navigation through the integration of satellite position fixing and other shipboard sensors with advanced, electronically-derived, chart information. Properly implemented, electronic charts have a tremendous amount to offer the mariner for effective, safe and efficient navigation. This paper seeks to identify the current legal status of electronic charts within the UK’s merchant shipping regulatory regime to ensure that shipping companies and mariners, taking advantage of such systems, do so within the law.